Studi Deskriptif Peningkatan Kompetensi Pedagogik Dan Sosial Guru Dalam Proses Belajar Mengajar Di Madrasah Diniyah Ihya Ulumuddin - Arif Kurnia; Reza Ahmad Zahid; Abbas Shofwan Matlail Fajar (Pascasarjana Institut Agama Islam Sunan Giri Ponorogo, 2026)
Teacher skills are essential in the learning process to prevent student boredom. To create effective and enjoyable high-quality learning, it is necessary to apply basic teaching skills. The instructional process will align with established goals if a teacher possesses a dynamic spirit, accountability, and discipline in facing various classroom challenges. This study aims to: 1) identify efforts to improve teachers' pedagogical competence regarding creativity in the teaching and learning process at Madrasah Diniyah Ihya’ Ulumuddin; and 2) identify teachers' social efforts in developing communication expertise during the teaching and learning process at Madrasah Diniyah Ihya’ Ulumuddin. This study employs a descriptive qualitative research method. The research was conducted at Madrasah Ihya’ Ulumuddin, located within the Darussalam Islamic Boarding School, Lirboyo, Kediri, East Java. Data analysis techniques included data reduction, data display, and conclusion drawing. Data validity was tested using the triangulation method. The results indicate that: 1) Teachers develop their creativity by implementing learning methods suited to student conditions, utilizing media to support the learning process, and sharing experiences with fellow teachers across various subjects. 2) At Madrasah Diniyah Ihya’ Ulumuddin, efforts have been made to establish open communication between teachers and students to identify obstacles and provide the best solutions. This approach helps students focus on the material presented, thereby improving the quality of learning. Based on the overall analysis, it can be concluded that there are ongoing efforts to enhance the pedagogical and social competencies of teachers at Madrasah Diniyah Ihya’ Ulumuddin, as evidenced by initiatives to improve creativity and communication skills. Consequently, it is expected that teacher professionalism will also increase